2021
DOI: 10.3390/nu13041186
|View full text |Cite
|
Sign up to set email alerts
|

Recipe Components and Parents’ Infant and Young Child Feeding Concerns: A Mixed-Methods Study of Recipe Posts Shared in Thai Facebook Groups for Parents

Abstract: Social media is increasingly becoming a significant source of information for parents, including about feeding young children. However, little attention has been given to the characteristics of recipes for infants and young children and how they interact with parental perceptions regarding food decisions shared by users on social media. Building on findings related to shared recipe components and parental food choices, between December 2019 and July 2020, this study retrospectively collected 80 shared recipes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…As facilitated by these social media functions, common child feeding practices in social media may evolve into social norms [20]. In our previous studies, we found that there were commonly shared practices around feeding age-appropriate food and seasoning, and food allergy awareness, which was disseminated within Thai Facebook groups in children's diets [10,23]. In the interviews, some mothers explained why they had adopted them.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As facilitated by these social media functions, common child feeding practices in social media may evolve into social norms [20]. In our previous studies, we found that there were commonly shared practices around feeding age-appropriate food and seasoning, and food allergy awareness, which was disseminated within Thai Facebook groups in children's diets [10,23]. In the interviews, some mothers explained why they had adopted them.…”
Section: Discussionmentioning
confidence: 98%
“…In-depth, semi-structured interviews were conducted during January 2021 and April 2021, using participants' preferred technology, mostly by voice call on the Line application. The interview guide (Appendix A) was constructed based on authors' previous studies [7,10,23]. All interviews were conducted in a private location where the conversation could not be seen or heard by others.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thailand, traditional weaning foods are rice and banana [ 22 ]. A study of modern feeding practices that analysed recipes shared on Thai online peer support groups revealed that animal-source foods were not commonly fed until children were aged eight months and older due to allergy concerns [ 23 ]. However, a recent literature review points to the role of delayed introduction of allergenic food in increasing the risk for allergy development [ 24 ].…”
Section: Discussionmentioning
confidence: 99%